The Implementation of Scientific Approach on Biology Learning Process Performed by Teachers - Siwi, Hefi Mardias; Wuryadi, Wuryadi (FMIPA UNNES, 2019)
This research was aimed to discover the implementation of scientific approach on biology learning process of X class in discovery learning model performed by teachers. The type of this research was descriptive by using a survey method. The sample was collected through convenience sampling. The population in this research was biology teachers in Bantul, and this sample was 4 biology teachers of X class in State High Schools of Bantul Regency. The instrument used in this research was a questionnaire, namely the questionnaire related to the perception of students toward the learning performed by teachers. The acquired data then analyzed descriptively by calculating the level of tendency of each learning aspect. The research results have indicated that the scientific approach in biology learning process of X class through discovery learning model has been implemented properly in accordance with the stages of discovery learning learning model.